Perbedaan Pola Makan dan Kejadian Anemia pada Masa Prakonsepsi di Daerah Pegunungan dengan Pesisir - Megayanti, I Gusti Putu Lian; Ani, Luh Seri; Sari, Komang Ayu Kartika (Universitas Udayana, 2022)
Anemia is a condition when the Hb levels is below normal. Anemia have a bad impact in pregnancy, this necessary prevented by paying attention to dietary habits since the preconception period. This study aims to determine differences in dietary habits and the incidence of anemia during preconception in mountainous and coastal areas. The method that used in this study is a cross-sectional analytic method. Samples included 200 preconception women aged 15-49 years in Banjar Kaja Serangan Denpasar and Banjar Kerta Payangan Gianyar and fulfilling the inclusion criteria. Primary data were taken by interviews on filling out the SQ-FFQ and measuring Hb levels using Hb meter. The variables include the incidence of anemia as the dependent variable, dietary habits, region, age, education, occupation, marital status, parity, and menstrual patterns as independent variables. Independent Sample T Test was conducted to determine differences in the incidence of anemia and dietary habits between mountainous and coastal areas. The results showed that there was no difference in the incidence of anemia in preconception women in mountainous and coastal areas. However, there are differences in the dietary habits of protein, vitamin E, vitamin B12, and iron among preconception women in mountainous and coastal areas. The dietary habits of preconception women in mountainous areas is different from those in coastal areas, so it is advisable to adjust the dietary habits of preconception women in each area to avoid anemia. Keywords : Anemia, Mountainous, Coastal Areas, Dietary Habits, Praconception